DAMPAK EKONOMI DIGITAL 4.0 TERHADAP KUALITAS SUMBER DAYA MANUSIA DI ERA PANDEMI COVID DI INDONESIA - Dian Rokhmawati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This article aims to describe the increase in the quality of human resources (HR) of the digital 4.0-based sharia economy during the Covid-19 pandemic. Two things are the focus of writing, including: the qualification of Islamic economic human resources based on digital 4.0 and how to improve the quality of these human resources during the Covid-19 pandemic. In order to meet digital 4.0-based Islamic economic human resources both in quality and quantity, it is necessary to meet qualifications in the form of soft skills and hard skills. Soft skills are related to character building, so faith, morals and sharia are needed which will be realized in all activities which are framed by the characteristics of shiddiq, tabligh, amanah, and fathonah. Meanwhile, hard skills include increasing knowledge and skills to create competent and expert human resources in their fields. Improving the quality of digital 4.0-based sharia economic human resources during the Covid-19 pandemic, namely through the national education system that combines offline and online learning, formal and informal education, socialization and campaigns for government programs to the community. The implementation is through academic channels from various levels or vocations or professions in all educational, social and religious institutions, as well as Islamic economics and finance. The academic path requires new efforts to respond to digital 4.0, namely digital literacy and technological literacy to realize literate human resources.